Control of Goods Inventory Uses the Accurate Program - Ashari, Muhammad Hasyim; Wanda Sofiatul Fauziah (Santoso Academy Network, 2024)
In this era of globalization, information systems play an important role in inventory management in trading, manufacturing and service companies. Inventory is an important asset that can generate profits through the production or sales cycle. CV Duta Survey Indonesia, a company engaged in sales, rental, service, and calibration of land measuring instruments, has a variety of products with stock coming from distributors. However, problems often occur related to recording and checking the stock of goods, which results in losses for the company. The system is needed to solve this problem can manage inventory well. CV. Duta Survey Indonesia has used the Accurate program for processing inventory data, but there are still things that need to be corrected in the inventory report. Therefore, the author will try to implement the accounting system with the Accurate program correctly. This community service activity aims to provide outreach and assistance regarding the use of the Accurate program in managing inventory properly, with the hope of improving the inventory administration system in the warehouse. The managerial implication in this research is that Accurate users help ensure accurate inventory data.